Pentingya 3R Dan PHBS Disekolah Sebagai Upaya Mewujudkan Kesadaran Lingkungan Dan Kesehatan Di Nagari Panampuang - Kurniawan, Rahmi; Siti Fatimah; Alfito Dimas Cahyadi; Arif Adrian (Manaruko: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this article is to educate students to have knowledge and awareness in separating waste based on its category and to be able to apply the habit of washing hands before activities From the results of observations, it appears that students experience a lack of understanding in separating waste according to its category and the lack of habit of washing hands before activities, this phenomenon has not been widely spread among students. The method of implementing this activity is by conducting 3R and PHBS socialization and demonstrating how to recycle waste into useful items. The solution to this problem is to carry out 3R and PHBS socialization to educate students about waste and clean and healthy living behavior, carry out waste sorting games with games, practice proper hand washing and carry out recycle used goods as an implementation of this socialization activity. The result of this activity is that students understand and are interested in carrying out waste selection actions and being creative with waste to become useful items